Phylogenetic conservation of the 3′ cryptic recombination signal sequence (3′cRSS) in the VH genes of jawed vertebrates - Sun, Yi; Liu, Zhancai; Li, Zhaoyong; Lian, Zhengxing; Zhao, Yaofeng (Frontiers in Immunology, 2012)
The VH replacement process is a RAG-mediated secondary recombination in which the variable region of a rearranged VHDJH is replaced by a different germline VH gene. In almost all human and mouse VH genes, two sequence features appear to be crucial for VH replacement. First, an embedded heptamer, which is located near the 3′ end of the rearranged VH gene, serves as a cryptic recombination signal sequence (3′cRSS) for the VH replacement process. Second, a short stretch of nucleotides located downstream of the 3′cRSS serve as a footprint of the original VH region, frequently encoding charged amino acids. In this review, we show that both of these two features are conserved in the VH genes of all jawed vertebrates, which suggests that the VH replacement process may be a conserved mechanism.